HIF1‐regulated ATRIP expression is required for hypoxia induced ATR activation. Issue 7 (20th February 2013) - Ding, Gang; Liu, He-Dai; Liang, Hong-Xiang; Ni, Ru-Feng; Ding, Zhao-Yan; Ni, Guo-Ying; Hua, Hong-Wei; Xu, Wei-Guo
Abstract : The ATR–ATRIP protein kinase complex plays a crucial role in the cellular response to replication stress and DNA damage. Recent studies found that ATR could be activated in response to hypoxia and be involved in hypoxia‐induced genetic instability in cancer cells. However, the underlying mechanisms for ATR activation in response to hypoxic stress are still not fully understood. We reported that ATRIP is a direct target of HIF‐1. Silencing the expression of HIF‐1α in cancer cells by RNA interference abolished hypoxia‐induced ATRIP expression. Silencing the expression of ATRIP by RNA interference abolished hypoxia induced ATR activation and CHK1 phosphorylation in cancer cells. Taken together, these data shed novel insights on the mechanism of hypoxia‐induced activation of the ATR pathway. Abstract : ► Hypoxia and hypoxia reagent induce ATRIP expression. ► HIF‐1 mediates hypoxia‐induced ATRIP expression. ► Identification and validation of a functional HRE in the ATRIP promoter region. ► Hypoxia‐induced ATR activation is mediated by ATRIP.